Effects of coat weight and pigment selection on flexographic printability of coated test liners - (:unkn) unknown (My University, 2010)
Coated linerboard continues to be a growing value-added market of interest to containerboard and corrugated markets. Development of coatings to improve the surface properties of Kraft and test liners continues to be important, as manufactures try to further improve the visual appearance of a printed box. In this study, the surface and print properties of a 100 g/m2 commercial test liner coated with different coat weights using different pigments and binders are compared. Coating, coat weight, PPS porosity, caliper, roughness, gloss, CIE whiteness and brightness are compared before and after calendering. The uncalendered and calendered samples were then printed with water based Performa Reflex Blue flexographic ink, using a laboratory K-proofer press. Ink density, print contrast, dot gain, dot roundness, delta gloss, and print mottle were then measured and compared. Results from the optical and print properties are related to the measured wetting and pigment packing properties of the coating. This study reveals that while coating and calendering positively affect print quality, coating weight did significantly affect print quality. Many of the print properties were influence by pigment type. Higher levels of kaolin addition resulted in an increase chroma and print density, and a decrease in print mottle. The use of CaCO3 increased print lightness, print delta gloss and print contrast, but lowered coating gloss.